PWE-045 Gastric polyps. (17th June 2017) - Babiker, M; Ahmad, I; Prabhakaran, S; Livett, H; Malik, A
Abstract : Introduction: Gastric polyps (GPs) are incidentally encountered during routine endoscopy. GPs are usually small and asymptomatic and can be sporadic or part of polyposis syndrome. Histologically GPs are classified as fundic gland polyps (FGPs), hyperplastic polyps (HYPPs) or adenomatous polyps (APs). British Society of Gastroenterology (BSG) guidelines recommend that all polyps should be biopsied and for HYPPs, Helicobacter Pylori (HP) should be checked and eradicated if present. Also for HYPPs and APs surrounding mucosa should carefully be examined and biopsied if needed. The aim of this study was to assess compliance with BSG guidelines. Method: A retrospective study was performed in which the gastro-intestinal reporting tool from July 2016 to December 2016 across two hospitals was searched for reports that mentioned GPs. Results: GPs were identified in 165 out of 3325 gastroscopies (4.9%) performed over 6 month period. 79 were male and rest female (86). The mean age was 61 (range 30–92 years). 143/165 (86%) patients had their GPs biopsied whereas no biopsies were taken from the remaining 22 (14%). Histologically most were FGPs 100/143 (69.9%) and the rest were reported as either HYPPs 27/143 (18.8%), normal gastric mucosa 7/143 (4.8%) or non-specific (inflammatory or regenerative changes) in 9/143 (6.2%). None of GPs were APs. Of the 27 hyperplastic polyps; HP was checked in 15 (55.6%), and the surrounding mucosa was not biopsied in any of these cases. Conclusion: - Gastric polyps are not uncommon. - Majority are FGPs followed by HYPPs. - In our study none of the patients had APs. - Compliance with BSG guidelines was not satisfactory as 14% of the patients had no biopsies taken and almost half of the patients with HYPPs did not have HP checked. Disclosure of Interest: None Declared